How Do You Feel? A Simple Visual Tool for Assessing Emotional Well-Being. Issue 3 (2021) - Weiler-Wichtl, Liesa J.; Fries, Jonathan; Schwarzinger, Agathe; Fohn-Erhold, Verena; Pletschko, Thomas; ., Ulrike Leiss
No abstract available